Teoria da empresa para o direito do trabalho brasileiro - Pragmácio Filho, Eduardo (2017)
The Brazilian employment law does not reflect a relationship to economics. The first objective of this thesis is to show the relationship between economics and labor law since the Brazilian Labor Code considers the firm as an employer. The second objective is to point out new directions concerning employers’ responsibilities with respect to business practices based on the notions of risk and power. The methodology adopted is the bibliographic research. This thesis depicts some of the most important economic approaches of firm theory, such as the neoclassical, the principal-agent, the transaction costs (Ronald Coase), the nexus of contracts and the property rights (Oliver Hart). The four profiles of the enterprise (Asquini) and the business risks (Simon Deakin), notions from corporate law, are also discussed. Then, the firm is discussed in relation to the workplace in order to identify some examples of what David Weil called the "fissured workplace", such as supply chains and franchises. As an employer, the firm exercises five functions through one or several legal entities, according to Jeremias Prassl’s theory. The employer’s functional approach is (in an implicit way) reflected in the Brazilian Labor Code and can be perfectly applied to Brazilian employment law for a better assignation of responsibilities to the various entities that carry out one or more of the employers’ functions. The firm is a power, it has a political profile and needs to self-regulate through codes of conduct or through a new system of responsibility. Finally, the conclusion reached is that the notions from law and economics, regarding transaction costs, nexus of contracts, property rights, the profiles of the enterprise found in Asquini’s theory, and the notions of power and risk create new legal tools to produce an innovative employment relationship responsibility